Student Mental Effort on Integrated Science Curriculum Content Analysis and Pedagogy - I. Permana; H. Firman; S. Redjeki; I. Hamidah; N. Safitri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
This study aims to determine the profile and outlook of prospective elementary school teachers on mental effort on Integrated Science curriculum materials integrated content and pedagogy as well as to know the pattern of integrated IPA curriculum analysis integrated content and pedagogy. The subjects of the research are prospective teachers of elementary school one of the universities in the city of Bogor semester 5 class of 2016/2017 as many as 31 students. The data needed to answer the problem of qualitative data. The data were collected with several techniques such as observation and questionnaires. The main questions asked in this study are the questions asked to prospective elementary school teachers. Principal questions asked to prospective teachers of elementary school, the question to reveal the mental business of prospective elementary school teachers in the curriculum analysis courses. Based on the results of research, applied lecture strategy resulted in low mental effort. In the curriculum analysis lectures found increased mental effort caused by material complexity.Keywords: mental effort, integrated science, integrated content and pedagogy lectures, curriculum analysis